BULLYING AMONG ELEMENTARY SCHOOL STUDENTS: A CASE STUDY OF ELEMENTARY SCHOOL-AGED CHILDREN IN NGEMBATPADAS VILLAGE - Nabila, Vita; Habiby, Wahdan Najib (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This study aims to identify the types, reasons, and handling of bullying with a qualitative case study approach. Primary and secondary data were collected through interviews and observations of 8 participants. Data analysis was done descriptively. Bullying is found in the form of verbal (mockery, nicknames, Rude words, demeaning, accusations of stealing) and physical (throwing, hitting, pushing and kicking, scratching, shocking or surprising). The reasons for bullying are jokes, lack of empathy, and jokes, and the victim's emotional reaction. Parents prevent it with preventive and persuasive communication, while teachers conduct socialization, religious approaches, cooperation with parents, installation of banners, and habituation of singing anti-bullying songs.